Increasing Company Productivity by Using the Green Productivity Method at PT. Mitra Agung Sawita Sejati - Dirjo Silaban; Uun Novalia Harahap; Yetti Meuthia Hasibuan (Publikasi Indonesia, 2025)
The concept of All-Gender Facilities has caused controversy in many countries, especially regarding the experience of users who feel uncomfortable with the presence of other genders in private spaces such as toilets and changing rooms. This study aims to explore the acceptance of the community in the Greater Jakarta area towards the All Gender Facility, especially in the use of toilets and changing rooms. A qualitative approach with a case study method is used to understand and analyze the response of society influenced by social and cultural norms. Data was collected through in-depth interviews with eight purposively selected informants. The results of the study show that awareness and first experience in using the All Gender Facility are influenced by the level of social media exposure and personal experience when using it. Security and hygiene factors, including space design and management, are the main elements that affect user privacy and comfort. Consideration of cultural norms in the implementation of the All Gender Facility has a very important role in community acceptance. The multicultural community of Greater Jakarta shows resistance to this concept due to cultural and religious considerations. However, in terms of functionality, this concept is acceptable on the condition of a design that pays attention to user privacy and security.